Changes in physiological activities are responsible for homoyessotoxin-induced toxicity in abalone Haliotis discus hannai. (July 2022) - Liang, Ye; Ni, Ziyin; Zhu, Tian; Yang, Jun; Ji, Nanjing; Mao, Tianyue; Gu, Haifeng
Abstract: Homoyessotoxin (homo-YTX) is a lipid-soluble toxin produced by toxic dinoflagellates. It is widely distributed in marine ecosystems worldwide, and it poses a threat to the survival of aquatic animals. The tissues of the abalone Haliotis discus hannai are easily damaged by homo-YTX during harmful algal blooms. In this study, H. discus hannai was exposed to homo-YTX (0, 2, 5, and 10 µg L −1 ) to evaluate the rates of survival ( S ) and death ( D ) and the antioxidative, metabolic, and digestive physiological responses in the gills and digestive gland of abalone. Homo-YTX decreased S and the activities of Na + /K + –adenosine triphosphatase, Ca 2+ /Mg 2+ –adenosine triphosphatase, superoxide dismutase, catalase, alkaline phosphatase, xanthine oxidase, lactate dehydrogenase, amylase, protease, and lipase. Meanwhile, D, the reactive oxygen species level, and the malondialdehyde content increased with increasing concentrations of homo-YTX. In addition, homo-YTX induced oxidative stress, enhanced the lipid peroxidation reaction, reduced the energy supply, and inhibited the metabolic and digestive physiological activities in the gills and digestive gland of abalone. Oxidative stress-mediated insufficient energy supply and physiological activity reduction caused the death of abalone. Highlights: Homoyessotoxin is harmful to the survival of abalone Haliotis discus hannai . Homoyessotoxin induces oxidative stress and lipid peroxidation in abalone. Insufficient energy supply in the tissues of abalone inhibits its survival. Changes in physiological activities are responsible for the toxicity of homoyessotoxin.